Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Masyarakat Pada Kantor Desa Padang Genting Kecamatan Seluma Selatan - Zaidil Akhirin; Ermy Wijaya; Iswidana Utama Putra (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to determine whether the dimensions of service quality at the level of reliability, responsiveness, assurance, empathy, physical evidence, affect community satisfaction at the Padang Genting Village Office, Seluma Selatan District. This research is a type of quantitative research. The sample in this study were 120 respondents/community. The results show that the results of the Multiple Linear Regression test Y = 30.534 – 0.224 (X1) + 1.880(X2) + -0.829(X3) + -1.667(X4) + 0.543(X5) + 3.423. Simultaneous test results in this study, accepting the hypothesis or accepting Ho and rejecting Ha means that there is a simultaneous influence between reliability (X1), responsiveness (X2), assurance (X3), empathy (X4), physical evidence (X5) on community satisfaction (Y) of 10,534. The results of the partial test tcount > ttable or 1,847 > 1,657 and the significance value is greater than 0.05, then the reliability hypothesis is accepted. The responsiveness variable (X2) at tcount > ttable or 5.899 > 1.657 and the significance value is greater than 0.05, then the hypothesis is accepted. guarantee variable (X3) at tcount > ttable or -3.421 > 1.657 and the significance value is greater than 0.05 then the hypothesis is accepted. the guarantee variable (X3) at tcount > ttable or -3.421 > 1.657 and the significance value is less than 0.05 then the hypothesis is rejected, meaning that there is no significant relationship between guarantee (X3) and community satisfaction (Y). Furthermore, empathy (X4) at tcount > ttable or -5.830 > 1.657 and the significance value is less than 0.05, the hypothesis is rejected, meaning that there is no significant relationship between empathy (X4) and community satisfaction (Y). and physical evidence (X5) at tcount > ttable or 3,041 > 1,657 and a significance value greater than 0.05 then the hypothesis is accepted, meaning that there is a significant relationship between physical evidence (X3) and community satisfaction (Y).